RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KELUARGA MISKIN - Ade Saputra; Dwi Kartini; Oni Soesanto (Lambung Mangkurat University, 2015)
Poverty is a difficult problem to be handled of. In that case, it’s necessary to have criteria on defining whether or not a family is in poverty. Unfortunately, until now, Karang Rejo Village at Jorong District of Tanah Laut Regency doesn’t have yet criteria with levels of prominence to make that decision. By that means, it’s necessary to make a decision support system that could support as alternative decision in defining the poverty level of each family in the Village. In the calculation on defining family poverty for the system uses MADM Yager Fuzzy Method. As for the system development uses the waterfall method. The result of this decision support system is a family data with classifications and levels of poverty. With the result that conclusion of this system is there’s a 40% difference between the system decision and the village representative’s. Keywords : Family Poverty, Fuzzy MADM Yager Kemiskinan merupakan permasalahan yang sulit untuk ditangani. Untuk itu diperlukan kriteria untuk menentukan apakah suatu keluarga itu termasuk miskin atau tidak. Sayangnya, sampai sekarang di Desa Karang Rejo Kecamatan Jorong, Kabupaten Tanah Laut belum memiliki kriteria dengan tingkat kepentingan untuk membuat keputusan tersebut. Untuk iitu diperlukan suatu sistem pendukung keputusan yang bisa menjadi keputusan alternatif pendukung dalam menentukan tingkat kemiskinan setiap keluarga di desa. Dalam perhitungan untuk menentukan tingkat kemiskinan keluarga digunakan metode Fuzzy MADM Yager. Sedangkan untuk pengembangan sistem digunakan metode waterfall. Hasil dari sistem pendukung keputusan ini adalah data keluarga beserta pengelompokan dan tingkat kemiskinan. Sehingga dari sistem ini didapatkan kesimpulan sebesar 40% perbedaan hasil antara keputusan yang dihasilkan sistem dengan keputusan dari pihak desa. Kata kunci : Keluarga Miskin, Fuzzy MADM Yager